Multipole expansion in generalized electrodynamics - Bonin, C. A.; Pimentel, B. M. [UNESP]; Ortega, P. H. (World Scientific Publishing, 2019)
In this paper, we study some classical aspects of Podolsky electrodynamics in the static regime. We develop the multipole expansion for the theory in both the electrostatic and the magnetostatic cases. We also address the problem of consistently truncating the infinite series associated with the several kinds of multipoles, yielding approximations for the static Podolskian electromagnetic field to any degree of precision required. Moreover, we apply the general theory of multipole expansion to some specific physical problems. In those problems, we identify the first terms of the series with the monopole, dipole, and quadrupole terms in the generalized theory. We also propose a situation in which Podolsky theory can be experimentally tested.
Keywords: magnetostatics and electrostatics; multipole expansion; Podolsky electrodynamics